Color stability of nano-filled, micro-hybrid, and silorane-based dental composite resin materials - Mohsen Saud M ALShetili; Mohammad Al-Omari (Wolters Kluwer Medknow Publications, 2016)
Aim: The purpose of this study was to investigate the color stability of nano-hybrid, micro-hybrid, and silorane-based composite resin restorative materials upon exposure to staining agents. Materials and Methods: One hundred twenty composites samples were prepared, 40 from each composite material (Filtek ® Z350, Filtek ® P90, and Filtek ® Z250). The specimens were randomly divided into four groups (10 of each sample). The specimens were incubated for 24 h in distilled water and then for 72 h in corresponding mediums (distilled water, red grape juice, green tea, coffee). The color of all the specimens was assessed before and after exposure with a spectrophotometer and total color change (ΔE) was calculated using ΔEFNx01 = [(ΔLFNx01)2 + (ΔaFNx01)2 + (ΔbFNx01)2]1/2. The data were analyzed with one-way analysis of variance (ANOVA) and Kolmogorov-Smirnov and the means of the solutions were compared by Tukey's honestly significant difference (HSD) (P < 0.05). Result: The lowest dicoloration was observed in Filtek ® LS P90 but it was not significant while the most discoloration was observed in Filtek ® Z350 and Filtek ® Z250. Also, coffee showed a highly significant (P > 0.05) discoloration compared with other media. Conclusions: Within the limitations of this study, it may be concluded that silorane-based composites are more resistant to discoloration than bis-GMA-based composites and coffee had the highest effect on composite discoloration compared to other media.